What are the most effective risk-reduction strategies in sport concussion?. Issue 5 (11th March 2013) - Benson, Brian W; McIntosh, Andrew S; Maddocks, David; Herring, Stanley A; Raftery, Martin; Dvořák, Jiří
Abstract : Aim: To critically review the evidence to determine the efficacy and effectiveness of protective equipment, rule changes, neck strength and legislation in reducing sport concussion risk. Methods: Electronic databases, grey literature and bibliographies were used to search the evidence using Medical Subject Headings and text words. Inclusion/exclusion criteria were used to select articles for the clinical equipment studies. The quality of evidence was assessed using epidemiological criteria regarding internal/external validity (eg, strength of design, sample size/power, bias and confounding). Results: No new valid, conclusive evidence was provided to suggest the use of headgear in rugby, or mouth guards in American football, significantly reduced players' risk of concussion. No evidence was provided to suggest an association between neck strength increases and concussion risk reduction. There was evidence in ice hockey to suggest fair-play rules and eliminating body checking among 11-years-olds to 12-years-olds were effective injury prevention strategies. Evidence is lacking on the effects of legislation on concussion prevention. Equipment self-selection bias was a common limitation, as was the lack of measurement and control for potential confounding variables. Lastly, helmets need to be able to protect from impacts resulting in a head change in velocities of up to 10 and 7 m/s in professional American and Australian football, respectively, as well as reduce head resultant linear and angular acceleration to below 50 g and 1500 rad/s 2, respectively, to optimise their effectiveness. Conclusions: A multifactorial approach is needed for concussion prevention. Future well-designed and sport-specific prospective analytical studies of sufficient power are warranted.